Unaccountable: How the Accounting Profession Forfeited a Public Trust - Brewster Mike (John Wiley & Sons, 2003)
For thousands of years, those who controlled and monitored society’s finances–accountants–were often the most powerful, respected, and influential members of the community. From the collectors at communal granaries in the ancient Middle East to the scribes who monitored Queen Victoria’s Exchequer, the accountant’s role has been to preserve the integrity of financial systems.